Meaning Realized on Online News About ‘France Under Attack’ - Anjar Setiawan; Dodi Mulyadi (Belajar Bahasa, 2021)
This research analyses the meaning realized on online news texts about ‘France under attack’ taken from The Jakarta Post, The Spectator, and Najam TV National. This is a descriptive qualitative research. The data were taken from the three news texts by classifying the clauses that related to the appraisal and then analyzing based on the subsystems of appraisal. The results showed that the news authors used three subsystems of appraisal included attitude, engagement, and graduation. In attitude, there were found the use of affect, judgement, and appreciation. There were also found of engagement consisted of monogloss and hetergloss. Further, the news items authors also applied graduation to make news more seems accurate.